Langmuir-Blodgett assembly of transparent graphene oxide-silver microwire hybrid films with an antibacterial property - Shi, Li-fang; Liu, Jun-zhe; Yang, Jun-he; Cai, Ling-fei; Shi, Li-yun; Qiu, Han-xun (New carbon materials, 2017)
Silver microwires (AgMWs) were made amphiphilic by non-covalent functionalization with poly (vinyl pyrrolidone) and hexadecyl mercaptan. The Langmuir-Blodgett (LB) technique was used to transfer graphene oxide (GO) and the functionalized AgMWs (F-AgMWs) onto a quartz substrate to obtain GO-AgMW hybrid films. The films had a high optical transparency and an antibacterial property against Escherichia coli (E. coli). It is proposed that the GO layer not only acts as an adhesive layer for AgMWs, but also is acidic, which provides an ideal reaction condition for AgMWs to release the Ag+ ions that fight E. coli. The influence of pH value on the antibacterial property of the hybrid films was investigated in order to verify the proposed mechanism. Further development of this method may provide a way to produce next generation transparent multifunctional thin films with antibacterial properties.